Sexually Dimorphic Scale Worms (Annelida: Polynoidae) From Hydrothermal Vents in the Okinawa Trough: Two New Species and Two New Sex Morphs - Zhang, Yanjie; Chen, Chong; Qiu, Jian-Wen (Frontiers in Marine Science, 2018)
Scale worms in the family Polynoidae are common inhabitants of both shallow-water and deep-sea ecosystems, but their diversity in the deep-sea remains poorly known. In the West Pacific, only 10 polynoid species have been described from deep-sea chemosynthetic ecosystems including hydrothermal vents and methane seeps. Here, we described two new species of polynoids based on specimens collected from hydrothermal vents in the Okinawa Trough. Levensteiniella undomarginata sp. nov. is distinguished from other congeners by having elytra with a wave-shaped edge, and that males possess two pairs of nephridial papillae. Branchinotogluma elytropapillata sp. nov. differs from other congeners by having papillae on the elytral edge, and by having a single pair of nephridial papillae and five pairs of C-shaped lamellae in males. Furthermore, we redescribed Lepidonotopodium okinawae (Sui and Li, 2017) and Branchinotogluma japonicus Miura and Hashimoto, 1991, because the original description of the former species did not cover males and that of the latter did not cover females. Sequencing of the cytochrome oxidase I (COI) gene in these four species confirmed the sexual dimorphism in vent polynoids for the first time, and provided reliable barcoding sequences for identifying these polychaetes.